Manajemen Personalia Dalam Meningatkan Kualitas Pendidikan Islam - Norma Fitria (Jurnal Bisnis Kreatif dan Inovatif, 2024)
Islamic education, as an effort to improve the quality of human resources, is an important sector that needs attention in supporting the achievement of national development goals. Through Islamic education, it is hoped that quality individuals can be formed who are able to contribute to achieving national development targets. Bearing in mind that national development requires superior human resources, both in general science and religion, attention, management and utilization of these human resources must be carried out optimally. In this research, the author formulates the problem: Is there a role for personnel management in improving the quality of Islamic education at Madrasah Tsanawiyah Ma'arif NU 08 Mataram Baru East Lampung in the 2022/2023 academic year? The aim of this research is to determine the role of personnel management in improving the quality of Islamic education at Madrasah Tsanawiyah Ma'arif NU 08 Mataram Baru East Lampung in the 2022/2023 academic year. This research sample included all teachers, staff and employees of Madrasah Tsanawiyah Ma'arif NU 08 Mataram Baru, totaling 42 people. To collect the necessary data, the author used several methods, including observation, interviews, questionnaires, and documentation. After the data was collected, the author analyzed it using the Contingency Coefficient Correlation formula. Based on data analysis from research results, it was found that there is a role between personnel management and the quality of Islamic education at Madrasah Tsanawiyah Ma'arif NU 08 Mataram Baru East Lampung in the 2022/2023 academic year.